A cross-sectional survey of environmental health in remote Aboriginal communities in Western Australia. Issue 5 (1st November 2016) - Melody, S. M.; Bennett, E.; Clifford, H. D.; Johnston, F. H.; Shepherd, C. C. J.; Alach, Z.; Lester, M.; Wood, L. J.; Franklin, P.; Zosky, G. R.
Abstract: Introduction : The Australian Aboriginal population experiences significantly poorer health than the non-Aboriginal population. The contribution of environmental risk factors in remote communities to this health disparity is poorly understood. Objective : To describe and quantify major environmental risk factors and associated health outcomes in remote Aboriginal communities in Western Australia. Methods : The association between environmental health indicators, community infrastructure and reported health outcomes was analysed using linear and logistic regression of survey data. Results : Housing/overcrowding was significantly associated with increased reports of hearing/eyesight (OR 3.01 95 % CI 1.58–5.73), skin (OR 2.71 95 % CI 1.31–5.60), gastrointestinal (OR 3.51 95 % CI 1.49–8.26) and flu/colds (OR 2.47 95 % CI 1.27–4.78) as health concerns. Dust was significantly associated with hearing/eyesight (OR 3.16 95 % CI 1.82–5.48), asthma/respiratory (OR 2.48 95 % CI 1.43–4.29) and flu/colds (OR 3.31 95 % CI 1.88–5.86) as health concerns. Conclusion : Poor environmental health is prevalent in remote Aboriginal communities and requires further delineation to inform environmental health policy.